Multicentric study of Tinidazol: Tinidazol en la prevención de infecciones anaerobias en cirugía colorectal - Praderi (h), Luis; Gerard, Juan; Berazategui, Ruver; Carriquiry, Guillermo; Croci, Fabio; Sanguinetti, Julio; Gateño, Nisso; Estefan, Alberto; Silva, Celso (Cirugía del Uruguay, 1987)
The efficiency of Tinidazol in the prevention of anaerobic infections in colorectal surgery is studied. Classified as 87,5% of contaminated surgery and 2,5% of soiled surgery, there weren't observad any case of anaerobic infections. The drug also preservad !he high.risk group representad by 44 patients with one or more factors predisposing to surgical infections.